The football encyclopedia - Williamson, Alicia; Jenkins, Liam (Sportswriter) (New York, NY : Kingfisher, 2024)
Presents an overview of the game of American football. Includes photographs.
Playing the game -- Football superstars -- Strategy -- Leagues -- Stadiums, fans, and business! -- Competitions.
Note to readers: The facts and statistics in this edition are accurate as of the 2023-2024 football season--Table of contents.
Includes index.
3-6
Keywords: Football -- Juvenile literature; Football; Sports -- Encyclopedias, Juvenile; Sports -- Juvenile literature; Encyclopedias; Football -- Encyclopedias, Juvenile